2023
DOI: 10.1021/acs.analchem.2c05456
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Vortex Generation, Pulsed Injection, and Rapid Mixing of Blood Samples in Microfluidics Using the Tube Oscillation Mechanism

Abstract: Here, we describe the generation of dynamic vortices in micro-scale cavities at low flow rates. The system utilizes a computer-controlled audio speaker to axially oscillate the inlet tube of the microfluidic system at desired frequencies and amplitudes. The oscillation of the tube induces transiently high flow rates in the system, which facilitates the generation of dynamic vortices inside the cavity. The size of the vortices can be modulated by varying the tube oscillation frequency or amplitude. The vortices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is worth noting that the rapid mixing of liquids can also be achieved using inertial microfluidic systems and active mechanisms. 26 Based on the centrifugal separation of plasma, we used centrifugal force to mix and drive the sample, automating the entire blood pretreatment process without an additional pump.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the rapid mixing of liquids can also be achieved using inertial microfluidic systems and active mechanisms. 26 Based on the centrifugal separation of plasma, we used centrifugal force to mix and drive the sample, automating the entire blood pretreatment process without an additional pump.…”
Section: Resultsmentioning
confidence: 99%
“…11 Thurgood et al reported a new mechanism for generating dynamic vortices in microfluidics at low static flow rates and demonstrated its application for cellular assays, fluid mixing, and pulsed injection. 12,13 new size-dependent particle trapping phenomenon in microvortices that enables tunable cell capture. 14 Liu et al proposed an acoustic microvortex-based strategy for cell capture, pairing, and fusion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Instead, microvortices are of great use to microfluidic systems because they are conducive to the manipulation of fluids and particles, which have been used for the rapid and controlled synthesis of functional nanomaterials and tunable processing and analysis of particulate samples (such as cells and colloids). , For example, Zhang et al proposed flower-like micromixers based on acoustic microvortices for developing ZnO nanorod arrays . Thurgood et al reported a new mechanism for generating dynamic vortices in microfluidics at low static flow rates and demonstrated its application for cellular assays, fluid mixing, and pulsed injection. , Khojah et al uncovered a new size-dependent particle trapping phenomenon in microvortices that enables tunable cell capture . Liu et al proposed an acoustic microvortex-based strategy for cell capture, pairing, and fusion .…”
Section: Introductionmentioning
confidence: 99%